Estrogen Modulates the Sensitivity of Lung Vagal C Fibers in Female Rats Exposed to Intermittent Hypoxia - Huang, Ya-Chen; Yuan, Zung Fan; Yang, Chang-Huan; Shen, Yan-Jhih; Lin, Jyun-Yi; Lai, Ching Jung (Frontiers in Physiology, 2018)
Obstructive sleep apnea is mainly characterized by intermittent hypoxia (IH), which is associated with hyperreactive airway diseases and lung inflammation. Sensitization of lung vagal C fibers (LVCFs) induced by inflammatory mediators may play a central role in the pathogenesis of airway hypersensitivity. In females, estrogen interferes with inflammatory signaling pathways that may modulate airway hyperreactivity. In this study, we investigated the effects of IH on the reflex and afferent responses of LVCFs to chemical stimulants and lung inflammation in adult female rats, as well as the role of estrogen in these responses. Intact and ovariectomized (OVX) female rats were exposed to room air (RA) or IH for 14 consecutive days. On day 15, IH enhanced apneic responses to right atrial injection of chemical stimulants of LVCFs (e.g., capsaicin, phenylbiguanide, and α,β-methylene-ATP) in intact anesthetized females. Rats subjected to OVX prior to IH exposure exhibited an augmented apneic response to the same dose of stimulants compared with rats subjected to other treatments. Apneic responses to the stimulants were completely abrogated by bilateral vagotomy or perivagal capsaicin treatment, which blocked the neural conduction of LVCFs. Electrophysiological experiments revealed that in IH-exposed rats, OVX potentiated the excitability of LVCFs to stimulants. Moreover, LVCF hypersensitivity in rats subjected to OVX prior to IH exposure was accompanied by enhanced lung inflammation, which was reflected by elevated inflammatory cell infiltration in bronchoalveolar lavage fluid, lung lipid peroxidation, and protein expression of inflammatory cytokines. Supplementation with 17β-estradiol (E2) at a low concentration (30 μg/ml) but not at high concentrations (50 and 150 μg/ml) prevented the augmenting effects of OVX on LVCF sensitivity and lung inflammation caused by IH. These results suggest that ovarian hormones prevent the enhancement of LVCF sensitivity and lung inflammation by IH in female rats, which are related to the effect of low-dose estrogen.